Female reproductive history and risk of type 2 diabetes: A prospective analysis of 126 721 women. Issue 9 (17th May 2018) - Pandeya, Nirmala; Huxley, Rachel R.; Chung, Hsin‐Fang; Dobson, Annette J.; Kuh, Diana; Hardy, Rebecca; Cade, Janet E.; Greenwood, Darren C.; Giles, Graham G.; Bruinsma, Fiona; Demakakos, Panayotes; Simonsen, Mette Kildevæld; et al.
Abstract : Aim: To examine the prospective associations between aspects of a woman's reproductive history and incident diabetes. Methods: We pooled individual data from 126 721 middle‐aged women from eight cohort studies contributing to the International Collaboration for a Life Course Approach to Reproductive Health and Chronic Disease Events (InterLACE). Associations between age at menarche, age at first birth, parity and menopausal status with incident diabetes were examined using generalized linear mixed models, with binomial distribution and robust variance. We stratified by body mass index (BMI) when there was evidence of a statistical interaction with BMI. Results: Over a median follow‐up of 9 years, 4073 cases of diabetes were reported. Non‐linear associations with diabetes were observed for age at menarche, parity and age at first birth. Compared with menarche at age 13 years, menarche at ≤10 years was associated with an 18% increased risk of diabetes (relative risk [RR] 1.18, 95% confidence interval [CI] 1.02‐1.37) after adjusting for BMI. After stratifying by BMI, the increased risk was only observed in women with a BMI ≥25 kg/m 2 . A U‐shaped relationship was observed between parity and risk of diabetes. Compared with pre‐/peri‐menopausal women, women with a hysterectomy/oophorectomy had an increased risk of diabetes (RR 1.17, 95% CI 1.07‐1.29). Conclusions: Several markers of a woman's reproductive history appear to be modestly associated with future risk of diabetes. Maintaining a normal weight in adult life may ameliorate any increase in risk conferred by early onset of menarche.